The Effect of Different Musical Tempos on Post-Exercise Recovery - Kapke, Justin; Keefe, Alexis; Perinovic, Emily; Schessler, Ben; Toy, Erik (Journal of Advanced Student Sciences (JASS), 2014)
Whether you choose to cruise to an electronic mix on a 5k run or head bob to classic rock in preparation for a lift on bench press, it is evident that listening to music while exercising has become a popular trend. Understanding the physiological effects created by music could reveal underlying reasons for this music-exercise integration. The purpose of this study is to determine whether fast and slow tempo music has an impact on post-exercise recovery rate. Twenty-eight healthy, 20-25 year old subjects participated by biking on a stationary bicycle until they reached a heart rate value that is twice their resting heart rate. Post-exercise recovery rate was determined based on data gathered on heart rate, breathing rate, and blood pressure for five minutes without music. This process was then repeated for each participant with the addition of either fast or slow tempo music during the post-exercise recovery time. The conclusion of this study revealed that fast tempo music caused a slower post-exercise recovery rate in terms of significant heart rate and breathing rate data. However, slow tempo music did not have a significant impact on postexercise recovery for heart rate and breathing rate. Blood pressure rate during post-exercise recovery also revealed no significance for neither slow tempo or fast tempo music.
An article that appeared in JASS, issue 2014
Keywords: aerobic; blood pressure; heart rate; breathing rate; exercise; recovery time; musical tempo